PENGEMBANGAN KOMPETENSI CREATIVE WRITING DALAM PEMBELAJARAN SASTRA DI PERGURUAN TINGGI - Putra Manuaba (LITERA, 2010)
This study aims to identify creative writing aspects and formulate a model for the development of creative writing competence. It was a qualitative study involving literature students from four universities in Surabaya. The data were collected through in-depth interviews. The findings show that only few students have writing experience. The learning model in the campus is one important aspect that can motivate students to write. An ideal model for the development of creative writing competence is one that integrates a variety of aspects that can develop creative writing. Some important aspects include (1) a creative writing course inliterature learning as a compulsory course at universities, (2) theory and practice (practice being more dominant than theory) for literature students, (3) attempts to make lecturers good at writing theory and practice, (4) reading enrichment in quality literary works, and (5) use of creative processes from high quality authors as inspiring part of creative work writing.